[18F]FDG PET/CT versus [18F]FDG PET/MRI for the diagnosis of colorectal liver metastasis: A systematic review and meta-analysis - Miao, Zhi; Zhao, Xiaomeng; Li, Xuanwen (Frontiers in Oncology, 2023)
Purpose The purpose of our meta-analysis and systematic review was to compare the diagnostic performance of [18F]FDG PET/CT and [18F]FDG PET/MRI in colorectal liver metastasis. Methods We searched PubMed, Embase, and Web of Science for eligible articles until November 2022. Studies focusing on the diagnostic value of [18F]FDG PET/CT or PET/MRI for colorectal liver metastasis were included. Using a bivariate random-effect model, the pooled sensitivity and specificity for [18F]FDG PET/CT and [18F]FDG PET/MRI were reported as estimates with 95% confidence intervals (CIs). Heterogeneity among pooled studies was assessed using the I2 statistic. The Quality Assessment of Diagnostic Performance Studies (QUADAS-2) method was used to evaluate the quality of the studies that were included. Results There were a total of 2743 publications identified in the initial search, finally, a total of 21 studies comprising 1036 patients were included. The pooled sensitivity, specificity, and AUC of [18F]FDG PET/CT in were 0.86 (95% CI: 0.76-0.92), 0.89 (95% CI: 0.83-0.94), and 0.92(95% CI: 0.90-0.94). [18F]FDG PET/MRI were 0.84 (95% CI: 0.77-0.89), 1.00 (95% CI: 0.32–1.00), and 0.89(95% CI: 0.86-0.92), respectively. Conclusion [18F]FDG PET/CT shows similar performance compared to [18F]FDG PET/MRI in detecting colorectal liver metastasis. However, pathological results were not obtained for all patients in the included studies and PET/MRI results were derived from studies with small sample sizes. There is a need for additional, larger prospective studies on this issue.